Effect of Sorption, Repeated Sorption and Desorption on Solubility and Swelling of the Poly(vinyl alcohol) Esters - NARKHEDE, B.N.; INGALE, R.B.; RATHOD, S.D.; RANE, P.H. (Asian Journal of Chemistry, 2010)
Series of polyesters prepared by partially esterification of poly(vinyl alcohol) and with different acid chloride viz., anthranilic acid, amino acetic acid and p-amino benzoic acid chloride. Solubility and swelling of these products in water have been evaluated. To study how the solubility and swelling of polyesters were affected by sorption, repeated sorption and desorption of the product of each series used for sorption once were carried out. The solubility (g/mL) and swelling degree (g/g) were calculated. When polyester resin dissolves in water every time the swelling degree of the undissolved polyester resin varies over a narrow range.